Transcriptionally active LTR retrotransposons in Eucalyptus genus are differentially expressed and insertionally polymorphic - Marcon, Helena Sanches [UNESP] (2015)
In Eucalyptus genus, studies on genome composition and transposable elements (TEs) are particularly scarce. Nearly half of the recently released Eucalyptus grandis genome is composed by retrotransposons and this data provides an important opportunity to understand TE dynamics in Eucalyptus genome and transcriptome. We characterized nine families of transcriptionally active LTR retrotransposons from Copia and Gypsy superfamilies in Eucalyptus grandis genome and we depicted genomic distribution and copy number in two Eucalyptus species. We also evaluated genomic polymorphism and transcriptional profile in three organs of five Eucalyptus species. We observed contrasting genomic and transcriptional behavior in the same family among different species. RLC_egMax_1 was the most prevalent family and RLC_egAngela_1 was the family with the lowest copy number. Most families of both superfamilies have their insertions occurring <3 million years, except one Copia family, RLC_egBianca_1. Protein theoretical models suggest different properties between Copia and Gypsy domains. IRAP and REMAP markers suggested genomic polymorphisms among Eucalyptus species. Using EST analysis and qRT-PCRs, we observed transcriptional activity in several tissues and in all evaluated species. In some families, osmotic stress increases transcript values. Our strategy was successful in isolating transcriptionally active retrotransposons in Eucalyptus, and each family has a particular genomic and transcriptional pattern. Overall, our results show that retrotransposon activity have differentially affected genome and transcriptome among Eucalyptus species.